Implementation Of Regulations In Handling Children In Conflict With The Law (ABH) - R. Khifti Yuliatun; Juwita, Juwita (Jurnal Scientia, 2024)
The implementation of the BAP by the police is not in accordance with Article 30 Paragraph (1) of Law No. 11 of 2012 concerning the Child Criminal Justice System and the Regulation of the Minister of State for Women's Empowerment and Child Protection of the Republic of Indonesia Number 15 of 2010 concerning General Guidelines for the Handling of Children Facing the Law, namely the facts in the field are contrary to the law. because the implementation is not only 24 hours, sometimes until the early hours of the morning when an investigation is carried out, this provision becomes contradictory because the rules and the implementation are not in line. Problem Formulation: 1) How is the Implementation of Regulations in Handling Children in Conflict with the Law (ABH)?, 2) How are the Sanctions for Law Enforcement Officials in Handling Children in Conflict with the Law (ABH) not in accordance with the Regulations?, Type of research: normative juridical, which is a study of legal principles, existing legal rules to obtain information related to this research. The author concludes: The application of laws and regulations in the juvenile justice system should be supported by various parties to ensure legal protection of the rights of children who are in conflict with the law, as well as there are no sanctions for law enforcement officials as article 30 paragraph (1) of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law) makes something ordinary.